Plant density and variety effect on yield, leaf spot disease, weed species richness and diversity of groundnut production in northern Ghana - Rahman, Nurudeen Abdul; Larbi, Asamoah; Tanzubil, Paul; Kizito, Fred; Hoeschle-Zeldon, Irmgard (2024)
Low plant density and weed infestation are major challenges for groundnut production in northern Ghana. A two-year on-farm study was conducted to determine the effect of plant density and variety on grain and fodder yields, incidence of leaf spot disease, weed species diversity and biomass. A factorial treatment combination of 6 varieties and 4 plant densities laid in strip plot design with 4 replications was used. The varieties were (early maturity type: Chinese, Yenyewoso, Samnut 23 and late maturity type: Azivivi, Manipinta, Samnut 22). The plants density included 9, 11, 15 and 22 plants/m2. The late maturity varieties recorded higher (p < .05) canopy cover, grain and fodder yields relative to that of the early maturity varieties. The late maturity varieties also recorded the least sedge weed species frequency, density and incidence of leaf spot disease compared with that of the early maturity varieties. The canopy cover, grain and fodder yields increased with increasing plant density. Broadleaf weed species frequency and density, weed biomass, richness, and diversity declined with increasing plant density. Grain yield showed negative and significant correlation with broadleaf weed species frequency, density and weed biomass. The results suggest that both early and late maturity groundnut varieties can be planted at a density of 22 plants/m2 to increase grain and fodder yields and reduce weed species richness, diversity and growth in northern Ghana and similar agro-ecology in West Africa.